2005
DOI: 10.1103/physreve.72.051716
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric study of the nematic to smectic-Aand smectic-Ato smectic-Cphase transitions in liquid-crystal–aerosil dispersions

Abstract: A high-resolution calorimetric study has been carried out on nanocolloidal dispersions of aerosils in the liquid crystal 4-n-pentylphenylthiol-4'-n-octyloxybenzoate (8S5) as a function of aerosil concentration and temperature spanning the smectic-C to nematic phases. Over this temperature range, this liquid crystal possesses two continuous XY phase transitions: a fluctuation-dominated nematic to smectic-A transition with alpha approximately alphaXY=-0.013 and a mean-field smectic-A to smectic-C transition. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
(88 reference statements)
2
13
1
5
Order By: Relevance
“…While the T c drifts have not been observed in the case of 8S5 + aerosil mixtures [11], they have been recorded in the case of calorimetric measurements of 7O.4 + aerosils [43]. The evolution of the C p shape to step-like for the χ = 0.20 sample, however, is in line with what has been reported for the 8S5 + aerosil mixtures [22]. On the contrary, the CE8 + aerosils mixtures exhibited a substantially different behavior where, analogously to the tilt angle, the heat-capacity profiles evolved into broadened and smeared supercritical anomalies as a function of increasing χ , with a rapidly decreasing enthalpic content.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…While the T c drifts have not been observed in the case of 8S5 + aerosil mixtures [11], they have been recorded in the case of calorimetric measurements of 7O.4 + aerosils [43]. The evolution of the C p shape to step-like for the χ = 0.20 sample, however, is in line with what has been reported for the 8S5 + aerosil mixtures [22]. On the contrary, the CE8 + aerosils mixtures exhibited a substantially different behavior where, analogously to the tilt angle, the heat-capacity profiles evolved into broadened and smeared supercritical anomalies as a function of increasing χ , with a rapidly decreasing enthalpic content.…”
Section: Resultssupporting
confidence: 87%
“…Extensive studies of the N -SmA transition of the thermotropic liquid crystal 4-n-pentylphenylthiol-4-noctyloxybenzoate (8S5) reveal that the critical character remains unaffected by the aerosil-introduced quenched-random disorder. Even though the N -SmA is a pseudotransition, due to the destruction of the quasilong-range smectic order, the critical exponents derived from high-resolution heat-capacity data remain three-dimensional XY -like, for a large range of nanoparticle concentrations included in the study [22]. In addition, investigating the effects of aerosils upon the smectic order of aligned and nonaligned gels of octylcyanobiphenyl (8CB), it was demonstrated that quenched randomness in aligned gels leads to constant three-dimensional XY critical exponents while otherwise a random field with disorder strength linearly dependent upon the nanoparticle concentration must be considered [9,[23][24][25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that high-resolution calorimetric data on 8 5 S +sil samples [16] show that the N-SmA transitions exhibit a critical variation in the excess heat capacity C p that, except for a narrow region of finite-size rounding, is as well-defined as that for the pure LC. Furthermore, the excess heat capacity associated with the SmA-SmC transition for LC+sil samples is smeared and rounded relative to the Landau mean-field behavior seen in pure 8 5 S , in qualitative agreement with the X-ray behavior observed here.…”
Section: Reflects This Distribution With Varying ( )  Ac T T I Valuementioning
confidence: 99%
“…1(a), is the primary order parameter of the SmC phase. Detailed high-resolution calorimetry work [16] on 4-n-pentylphenylthiol-4'-n-octyloxybenzoate ( 8 5 S ) in aerosil gels shows that both the N-SmA and SmA-SmC phase transitions are dramatically affected by the presence of the aerosil gel. In contrast to the calorimetry work, Clegg et.…”
Section: Introductionmentioning
confidence: 99%